2020
DOI: 10.3892/mmr.2020.11684
|View full text |Cite
|
Sign up to set email alerts
|

CSN1 facilitates proliferation and migration of hepatocellular carcinoma cells by upregulating cyclin A2 expression

Abstract: Constitutive photomorphogenesis 9 signalosome subunit 1 (CSN1) plays an important role in the ubiquitin-proteasome pathway and regulates various cellular processes, such as the cell cycle and DNA repair. The CSN complex consists of eight subunits (CSN1 to CSN8) and regulates the tumorigenesis of a variety of tumor types. However, the exact role of CSN1 in hepatocellular carcinoma (HCC) remains unclear. The present study evaluated the expression and biological effects of CSN1 in HCC tissue samples and cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…34 A report showed that CSN1 could enhance the proliferative and migrated abilities of MHCC-LM3 cells by upregulating CCNA2 expression. 35 Moreover, CCNA2 is active in the cytoplasm to activate PLK1 during the S/G2 transition. 36…”
Section: Discussionmentioning
confidence: 99%
“…34 A report showed that CSN1 could enhance the proliferative and migrated abilities of MHCC-LM3 cells by upregulating CCNA2 expression. 35 Moreover, CCNA2 is active in the cytoplasm to activate PLK1 during the S/G2 transition. 36…”
Section: Discussionmentioning
confidence: 99%
“…However, ubiquitination of substrates by APC/C requires activation or co-activation of CDC20 or CDH1 [ 46 , 47 , 48 ]. In addition to CCNA2 regulating cell proliferation by binding with CDC20 [ 49 ], CCNA2 is also regulated by CSN1 (signalosome subunit 1) in an ubiquitination-independent manner, which affects the proliferation and migration of hepatocellular carcinoma cells [ 50 ]. Surprisingly, the PPI network ( Figure 5 ) showed that the proteins controlling cell cycle progression (mRNAs were down-regulated, according to sequencing results) can interact with ubiquitin-proteasome-related proteins (mRNAs were up-regulated), which implies that ubiquitination of cell cycle-related proteins (such as CCNA2 and CDC20) determines cell development, and ubiquitination plays an indispensable role in the regulation of yak preadipocyte proliferation and differentiation by lncFAM200B .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MGB1 and cyclins contributed to the regulation of the migration and invasion abilities of resistant cells. A previous study reported that the upregulation of cyclin A2 enhanced the migration of hepatocellular carcinoma (HCC), while its downregulation decreased the migration of DLD‐1 and SW620 colorectal cancer cell lines (CRC) [ 38 , 43 ]. Cyclin D1 enhances cell migration and invasion activity in fibroblasts by regulating RhoA [ 33 ] as well as tumor cells [ 34 , 35 , 44 ].…”
Section: Discussionmentioning
confidence: 99%